Were universal banks more vulnerable to banking failures? Evidence from the 1931 German banking crisis - Müge Adalet (TÜSİAD-Koç University Economic Research Forum, 2009)
This paper examines the 1931 German banking crisis using a bank-level data set. It specifically focuses on the link between banking structure and financial stability. The universality of banks, a key characteristic of the German banking system, is shown to increase the probability of bank failure after controlling for other bank-level characteristics and macroeconomic variables.
Keywords: N24; E44; G01; 330; Banking Crises; Great Depression; Universal Banking; Bankenkrise; Universalbank; Bankgeschichte; Deutschland (bis 1945)